Novos complexos de prata(I) com fenil e difenilfosfinato - Ceolin, Joice (2013)
New compounds phenylphosphinates and diphenylphosphinates silver (I) were synthe-sized and characterized with two coordination polymers and five molecular coordination complexes. The phosphinates are in oxygen-metal strong interactions due to the polarity of the P-O bond, and thus, they become good ligands in the formation of polymer chains in the solid state with a large number of monovalent metal centers Ag(I). Two precusores polymer were synthesized in order to study the properties of the metal center with phosphinic ligands: catena-poly[silver(I)-μ-diphenylphosphinate], 1 and phyllo-poly[silver(I)-μ-phenylphosphinate] 2, the from their metal complexes were formed aqua-κO-difenilfosfinato-κO-bis(triphenylphosphine-κP)silver(I) 3·H2O, 3·½ H2O·½C3H6O, aqua-κO-phenyilphosphinate-κO-bis(triphenylphosphine-κP)silver(I), 4, isopropanol-κO diphe-nylphosphinate-κO-bis(triphenylphosphine-κP)silver(I), 5, and di-μ-chloro-2:3κ2Cl-diphenylphosphinate-1κ2O,O'-tris{μ-bis(diphenylphosphine)etane}-1:2κP,P';1:3κP,P';2:3κP,P'-trisilver(I), 6. All compounds have the metal center silver(I) with distorted tetrahedral geometry at the packaging structure which might also reduce some bond lengths and angles. The compounds were characterized by various analytical techniques whenever possible the amount of sample available. Among them: melting point, elemental analysis of carbon and hydrogen, IR spec-troscopy, scanning electron microscopy, thermogravimetric analysis, X-ray diffraction single-crystal and X-ray diffraction powder.